2021
DOI: 10.1002/cbic.202100459
|View full text |Cite
|
Sign up to set email alerts
|

Novel Antibacterial Targets in Protein Biogenesis Pathways

Abstract: Antibiotic resistance has emerged as a global threat due to the ability of bacteria to quickly evolve in response to the selection pressure induced by anti‐infective drugs. Thus, there is an urgent need to develop new antibiotics against resistant bacteria. In this review, we discuss pathways involving bacterial protein biogenesis as attractive antibacterial targets since many of them are essential for bacterial survival and virulence. We discuss the structural understanding of various components associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 235 publications
(259 reference statements)
0
3
0
Order By: Relevance
“…Infectious diseases rank as the second leading cause of global mortality, with particular concern arising from panresistant strains of Gram-negative bacteria [4]. Target-based antibiotic development has not yielded significant breakthroughs, necessitating a greater emphasis on target-based antibiotic research [5].…”
Section: Introductionmentioning
confidence: 99%
“…Infectious diseases rank as the second leading cause of global mortality, with particular concern arising from panresistant strains of Gram-negative bacteria [4]. Target-based antibiotic development has not yielded significant breakthroughs, necessitating a greater emphasis on target-based antibiotic research [5].…”
Section: Introductionmentioning
confidence: 99%
“…Currently used antibiotics act on one of the pathways necessary for the survival of bacterial cells, including cell wall synthesis and the biosynthesis of nucleic acids or proteins. Due to the rapidly developing antibiotic resistance (e.g., production of enzymes inactivating antibiotics, modifications in the targeted pathways), it is important to select new biochemical and therapeutic targets for antibacterial drugs [5,20]. An interesting approach is to block the biosynthesis of peptidoglycan, the main component of the bacterial cell wall, not by targeting membrane-bound extracellular enzymes but at the cytoplasmic stage of biosynthesis by inhibiting Mur enzymes, which are essential for bacterial survival [21].…”
Section: Introductionmentioning
confidence: 99%
“…[17] Bacterial SRP is a ribonucleoprotein complex comprised of a 4.5S RNA and a Ffh protein, which along with its receptor protein (known as FtsY) mediates the co-translational translocation of nascent membrane and secretory proteins to the plasma membrane. [18][19][20][21][22] Two sequence-specific PNA molecules were designed to target the 4.5S non-coding RNA near the Ffh binding site. PNA1 was 9-mer, while PNA2 was 8-mer in length (referred to as PNA 9 and PNA 8 respectively in this paper (Figure 1A and Table S1).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we have reported PNA mediated inhibition of the bacterial Signal Recognition Particle (SRP) via inhibition of an essential RNA‐protein interaction [17] . Bacterial SRP is a ribonucleoprotein complex comprised of a 4.5S RNA and a Ffh protein, which along with its receptor protein (known as FtsY) mediates the co‐translational translocation of nascent membrane and secretory proteins to the plasma membrane [18–22] . Two sequence‐specific PNA molecules were designed to target the 4.5S non‐coding RNA near the Ffh binding site.…”
Section: Introductionmentioning
confidence: 99%